Ethical Differences Between Loan Maturity Mismatching and Fractional Reserve Banking: A Natural Law Approach - Davidson, Laura (2015)
In a number of recent articles, the debate on the ethics of fractional reserve “free” banking has been extended to loan maturity mismatching, specifically the banking practice of borrowing short and lending long. Barnett and Block (J Bus Ethics 88(4):711–716, 2009; 2010) claim the practice is illicit, because like fractional reserve banking it creates duplicate property titles. They argue there is a continuum in the time dimension between the two kinds of activities. Bagus and Howden (J Bus Ethics 90(3):399–406, 2009; 106(3):295–300, 2012a; Eur J Law Econ, 2012b; Bus Ethics 22(3):235–245, 2013) maintain that loan maturity mismatching does not create duplicate titles and is not illicit, and that from an economic and legal perspective there is no continuum with fractional reserve banking. Cachanosky (J Bus Ethics 104:219–221, 2011) and Evans (J Bus Ethics, 2013) enter the debate from the free-banking standpoint and view both practices as legitimate. In this paper, I agree with the conclusions of Bagus and Howden, but adopt a different approach to support this position. Using the title-transfer theory of contract, I demonstrate from first principles why loan maturity mismatching does not create duplicate property titles and is a legitimate practice. Employing this same theory, I then present a novel argument to show why the contractual arrangements found in fractional reserve banking are logically contradictory and illegitimate.
Keywords: Natural Law; Demand deposits; Loans; Title-transfer theory of contract; Fractional reserve banking; Loan maturity mismatching; private property rights